INDEPENDENT COMPONENT ANALYSIS OF EVOKED POTENTIALS TO ESOPHAGEAL STIMULATION - Ying, Windy Li Jian (My University, 2001)
Cortical evoked potential to electrical stimulation of the esophagus is a relatively novel modality and is a useful clinical tool. Evoked Potentials (EP) represents the bioelectrical response of the brain elicited by an external sensory stimulation to either an organ or a receptor. Since the physiological study suggests that there are several neuronal sources involved, the EP signal is a mixture of their responses. The traditional way of directly measuring the signal recorded by the electrodes is similar to trying to listen to a group of people speaking at the same time. A lot of information might be lost if we can not pickup the information from each individual. Independent Component Analysis (ICA) is a new technique that can extract the signals according the independence of the sources. It can separate the recorded EP signal into different components given sufficient number of input channels. In this research we apply ICA to 41 sets of esophageal EP signals recorded from twenty channels in 8 human subjects. We test the reproducibility of the algorithm and compare the components arising from periodic and random stimulation protocol from these subjects. The results show that EPs and their independent components are reproducible. Four pairs of component pairs are found and their scalp distribution maps and activation waveform provide interesting information for further study. Also, ICA isolate and extract a widely distributed stimulus artifact as a single output component, and remove it from the reconstructed signal . These results demonstrate that ICA could parsimoniously decompose esophageal EP signals into temporally independent, spatially fixed, and physiologically plausible components. ICA opens a new window to study the esophageal EP signal and provides new information that we were not able to obtain from other signal-processing techniques. Electrical stimulation (ES) of the esophagus can also be used to study the afferent and efferent pathways of human subjects. In a study of 7 patients with gastroesophageal reflux disease, 9 patients with noncardiac chest pain and 12 controls we found clinically useful information during electrical stimulation of the esophagus. Patients with NCCP had low amplitude cortical EP with increased vagal response during ES when compared to controls. Patients with GERD had high resting sympathetic tone and normal EPs but lower vagal response to ES when compared to normal subjects.
Keywords: Esophagus; Evoked potentials; Independent Component Analysis; Electrical stimulation; Esophageal signal; GERD